Indicators for scientific articles - Lesiów, Tomasz; Xiong, Youling; Chin, Koo (Kryteria jakości artykułów naukowych, 2019)
The publication of original research findings in peer-reviewed scientific journals is an important aspect of academic achievements and contribution to the society. Yet, failures to adhere to journals’ guidelines and standards are a common reason for the rejection of submitted manuscripts. The aim of this paper is to present the most important formal principles that researchers must comply with if they want their work to be printed in a refereed journal relating to food and food technology. The paper presents the results collected by three journal editors. Each of the coauthors recorded and analyzed his own latest reviews and then determined the most common errors in them by following a list of ten accepted rules and calculated the frequencies of recorded manuscript errors. The results showed consistent observations between the three coauthors. It is determined that the most often committed errors or non-compliances are poor experimental design, lack of innovation, and poor writing.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2019, Nr 4 (35), s. 42-57
Keywords: scientific articles; formal errors; Pareto-Lorenz method; publikacje naukowe; błędy formalne; metoda Pareto-Lorenza